1257 Low Nocturnal SpO2 and Daytime Sleepiness in a Child. (27th May 2020) - Pi, M Y; Han, F
Abstract: Introduction: Patients with nocturnal oximetry shows SpO2 during sleep of ≤ 90% in children for ≥ 5 minutes and sleep related hypoventilation is not documented could be diagnosed as sleep related hypoxemia (ICSD-3). However, known physiological causes should be indicated. Report of Case: A 5-year-old Chinese boy was referred to sleep lab for daytime sleepiness for three months. Type I narcolepsy was confirmed. Nocturnal PSG indicated a continuous low SpO2 baseline around 82%, with a nocturnal mean SpO2 of 83%, but no respiratory events. Voluntary hyperventilation made SpO2 increase from 83% to 95%, and hypoventilation syndrome was considered. PtcCO2 during PSG maintained 40mmHg, and no sleep related elevation observed. BPAP treatment had no effect on both SpO2. No dyspnea was complained. When he was 12 years old, follow-up PSG and MSLT indicated narcolepsy remained. During the past 7 years, no comorbidities occurred. Hb 104 g/L, RBC 3.53 × 1012/L, Hct 31%. ABG showed SaO2 of 97%, PaO2 98mmHg and PaCO2 40mmHg. Inconsistency between SpO2 and SaO2 reminds the existence of abnormal hemoglobin. A positive isopropanol precipitation test and further hemoglobin electrophoresis showed abnormal Hb and HbA were 37.6% (normal 0%) and 58.4% (normal 94.3–98.5%), respectively, but HPLC did not identify. Spectrophotometric analysis indicated that the absorption spectra were significantly different at 450nm~540nm and 600nm~1000nm. Hemoglobin structure analysis found the abnormal site. Gene sequencing identified a novel HBB: c.212 C>A mutation, resulting in amino acid 71 to change from alanine(Ala) to aspartic(Asp) acid as a de novo mutation. A diagnosis of Hemoglobin Seattle [β71:Ala→Asp；HBB:c.212C>A] was confirmed. Conclusion: Pediatric sleep medicine has a rapid development. Before a diagnosis of sleep related hypoxemia is made, in rare situation, abnormal hemoglobin should be considered.